17,21-SECOHOPANOIC ACIDS, 25-NORHOPANOIC ACIDS, AND 28-NORHOPANOIC ACIDS IN SOURCE ROCKS AND CRUDE OILS - Pan X.; Philp R.P. (My University, 2006)
The presence of three families of hopanoic acids, 17,21-secohopanoic acids, 25-norhopanoic acids, and 28-norhopanoic acids, is discussed. Oils from West Siberia and tar balls from the Seychelles Islands were found to contain relatively high proportions of 17,21-secohopanoic acids. These acids have not been previously reported in any oils or source rocks. A heavily biodegraded West Siberian oil, was found to contain an homologous series of 25-norhopanoic acids co-occurring with the 25-norhopanes as previously reported in only a small number of oils from Campos Basin, Brazil. 28-Norhopanoic acids have been reported in various sediments and extracts of the Monterey Shale, but in this study their occurrence has been extended to oils, degraded oils, and tar balls sourced from the Monterey Shale. The primary purpose herein is to report the occurrence of these acids and possible relationships between the acids and corresponding hydrocarbons. © 2006 Elsevier Ltd. All rights reserved.